TECHNOLOGY, PRODUCTION STRUCTURE AND DEVELOPMENT: A STUDY BASED ON NETWORK AND COMMUNITY ANALYSIS (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
The manufacturing industry was traditionally considered the “modernizing” sector of the economy. However, with the growth of knowledge-intensive services and the resource-based development experiences, its role has been questioned. The article aims to identify and characterize the relationship between the income level of the countries and their productive structure, with a particular focus on manufacturing activities. A network analysis method was used to analyze a database of 57 countries at a level of 34 industries. We identified “communities” of countries grouped by the level of similarity of their productive structures. Here, we observed a strong correlation between the income level and the productive structure of countries. Then, building upon a sectoral taxonomy based the technological intensity of activities we found that high income countries, despite having undergo- ne a deindustrialization process, maintained a productive and commercial specialization –as well as in their research and development activities– in knowledge-intensive manufacturing activities. By contrast, countries with lower income levels –particularly middle-income economies–, experienced a process of deindustrialization with a relative specialization in less knowledge- intensive activities.
Keywords: Economic development, Productive structure, Manufacture, Services